2005
DOI: 10.1097/01.cco.0000167735.26454.79
|View full text |Cite
|
Sign up to set email alerts
|

Communication in palliative care: a review of recent literature

Abstract: Themes included the education of health care providers, the need to care for carers, and interdisciplinary communication. Little attention was given to the growing population of elderly patients. Observer-based studies are unfortunately scarce, making the practice of palliative communication unseen. Finally, few studies report the cost-effectiveness of palliative care interventions though such studies may enhance palliative care and convince policy makers of the need to support such care. More empirical work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 47 publications
1
31
0
6
Order By: Relevance
“…This supports findings that communication falls into five main themes: information exchange; decision making; giving advice; and handling emotions, all of which were mentioned by our participants. 29 …”
Section: Discussionmentioning
confidence: 99%
“…This supports findings that communication falls into five main themes: information exchange; decision making; giving advice; and handling emotions, all of which were mentioned by our participants. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated favorable effects of an adequate information sharing process on coping, improved psychological condition, and higher quality of life [223][224][225][226][227].…”
Section: Strength Of Consensus: 96%mentioning
confidence: 99%
“…Because of this, the desire on the part of families to withhold information probably constitutes a greater source of friction in a PCU than in other types of units, where caregivers more frequently renounce giving information. -Maintaining hope clearly emerges as a fundamental component in patient and especially family satisfaction concerning information, a result also found in the literature (Innes & Payne, 2009;de Haes & Teunissen, 2005). Even when all appears lost, many people still want to believe in a "miracle" (Kirk et al, 2004).…”
Section: Interpersonal Skills: Associating Patients and Families Withmentioning
confidence: 54%
“…to that of listening (how does one listen?). More generally, the confidence patients and families have in caregivers is a major factor in building a solid caring relationship (de Haes & Teunissen, 2005), as is the degree of empathy found in that relationship (Schaefer & Block, 2009). Other factors should also be encouraged here, such as talking to patients fairly early about palliative care (when the illness is not too far advanced and they still feel well) or the prioritising of key points to discuss with them (Ngo-Metzger et al, 2008).…”
Section: Interpersonal Skills: Associating Patients and Families Withmentioning
confidence: 99%